Le français, langue du lieu ou langue d’ailleurs? Le discours sur le francoprovençal dans Le peuple valdôtain (2000-2018) - Meune, Manuel (Ponti/Ponts, 2021)
In the Aosta Valley, the French language has an ambiguous role despite its (co-)official status in the autonomous region. Not only does it have to compete with Italian, the dominant language, but its legitimacy must also be asserted in the face of Francoprovençal (‘Patois’). We will discuss the features of Francoprovençal as a relatively recently ‘discovered’ language, as well as the question of the status (both official and symbolic) of French in the Valley. There is a tension between the rights inherited from Aosta’s centuries-long Savoyard (i.e. ‘francotropic’) history, the aftermath of the Italianization that started in the 19th century, and the status of ‘language of the heart’ assigned to Patois – within a diglossic framework where Italian has long become the ‘high variety’. Our corpus is made up of texts published in the weekly newspaper Le peuple valdôtain, between 2000 and 2018. All texts include at least one occurrence of the keyword ‘patois’ or ‘francoprovençal’. The aim is not to study the social groups producing the discourse, but to look at the representations of Francoprovençal and, therefore, of French. One can observe for instance that one of the functions of Patois, constructed as historically close to France’s common language, is to legitimize the political status of French in the Aosta Valley – a language that, unlike Patois, is often perceived as ‘foreign’.